Pengaruh Profitabilitas, Solvabilitas, dan Opini Audit terhadap Audit Delay: Studi Empiris pada Perusahaan yang Terlambat Menyampaikan Laporan Keuangan Auditan ke BEI Tahun 2020-2023 - Putri Ray, Afifah Nazhirah; Taqwa, Salma (Universitas Negeri Padang, 2025)
This study examines the influence of profitability, solvency, and audit opinion on audit delay in companies listed on the Indonesia Stock Exchange from 2020 to 2023. The novelty of this study from the previous study lies in using Debt to Asset Ratio (DAR) as a proxy for solvency and emphasizing audit opinion as an independent variable. The sample selection method uses purposive sampling, using data from 304 companies consistently delaying audited financial reporting, this research applies multiple linear regression analysis to test the hypotheses, assisted by the SPSS version 26 program. The results reveal that profitability and audit opinion negatively affects audit delay. Conversely, solvency do not have a significant impacts on audit delay. These findings provide insights for regulators and practitioners to enhance corporate transparency and investor confidence. For further research, it isrecommended to select other variables that affect audit delay.